A Study of the Marketing Problems of Mango Growers (Using Factor Analysis) in Madurai District, Tamil Nadu - Anandaraj, P.; Chinniah, V. (Indian Journal of Marketing, 2011)
Cultivation of fruits contributes to the health, happiness and prosperity of the people. The standard of living of the people can be judged by production and consumption of fruits per capita. Mango, the world's most luscious fruit, has been recognized as the "king of fruits" long back. The area and production of fruits in general and mango, in particular, has increased many folds during the last fifteen years. This has also brought in many problems with regard to marketing of the fruits. The various marketing facilities necessary for economic disposal of the produce have, however, not been able to keep pace with the fast expanding fruit industry. The returns from mango cultivation depend on, along with several other factors, the quality of fruit, which in turn is determined by the time of picking, care taken in grading and packing, time taken in transportation and the like. The packing material has also become a problem with the increase in production of mango in the district. Keeping all these in mind, the major marketing problems of the mango growers are discussed in detail in this paper.